PENGARUH E-SERVICE QUALITY DAN E-WORD OF MOUTH TERHADAP PURCHASE INTENTION PRODUK EXILE - Alexander, Kevin Martin; Efrata, Tommy Christian; Kristanti, Lili (Universitas Ciputra Surabaya, 2023)
The purpose of this research is to find out the effect of e-service quality and e-word of mouth on purchase intention of Exile product. This research uses quantitative approach. The sample that is used is 384 respondents from male and female population who are from 17 to 30 years old that have purchased online fashion product in Indonesia. To answer the problems in this research, the writer uses helping tool like SPSS. The advantage of this research gives e-service quality and e-word of mouth affect on purchase intention, good service and review that are read by others before buying a product can increase people's trust to purchase decision even with the development of internet technology, people will be easier to receive information. The results of this research are e-service quality and e-word of mouth also affect significant on purchase intention. This research is expected to be able to support or create new understanding about e-service quality and e-word of on purchase intention. This research is also expected to be reference source for other research.